Investigating the Use of Metadiscourse Markers by American and Indonesian Writers in Opinion and Business Articles - Ardi Nugroho (Universitas Bunda Mulia, 2020)
Metadiscourse is an integral element of writing since it helps writers to organize and shape their arguments, but at the same time reflect their stance towards both the content and readers. There have been numerous studies concerning metadiscourse markers. However, little research has been done where Americans are directly compared with Indonesians. Furthermore, most of them have focused more on opinion, editorial, and sport articles, but not many have examined business ones. Considering this situation, the writer has become interested in investigating whether there are similarities and differences between how American and Indonesian writers incorporate metadiscourse markers in their opinion and business articles. The data for this research is taken from articles from two online newspapers, i.e. Washington Examiner and The Jakarta Post with a corpus size of 7,000 words for each type of article. The AntConc software version 3.5.6 by Anthony (2018) is used to analyze the data. The findings of the study reveal that there are some similarities and differences in the way American and Indonesian writers employ these markers in the writing of opinion and business articles.